From germination to propagation: Two decades of Strategy-as-Practice research and potential future directions - Jarzabkowski, Paula; Seidl , David; Balogun, Julia (Human relations (New York), 2022)
Over the last two decades, Strategy as Practice (SAP) has developed from an embryonic, fringe perspective on strategy to a consolidated field of strategy research. The 2007 special issue of Human Relations on ‘Strategizing: The challenges of a practice perspective’ played a pivotal role in bringing this field to fruition. Reflecting on the broad SAP aim to ‘let a thousand flowers bloom’, we employ a plant-based metaphor, to distinguish three phases in the development of SAP, each associated with different types of agenda work. In an initial Germination Phase, scholars did agenda-seeking work of establishing new concepts and differentiating SAP from other fields of strategy research. A Blossoming Phase of agenda-setting work followed, establishing a community of scholars and articles that identified as SAP, and establishing and defending the boundaries of the new field. As the field became established, it entered a Harvesting Phase, characterized by agenda-confirming work of using SAP lenses to explain core strategy and organization. Based on these reflections, and considering the many public critiques of SAP, we note that the field appears to be in transition to a new Propagating Phase that offers exciting potential to cross-pollinate within the SAP field and across other areas.